CIRC-0008798 and CIRC-0035967 as novel biomarkers in oral lichen planus and oral squamous cell carcinoma (Acta Scientiarum. Health Sciences, 2024)
Emerging evidence has indicated that circRNAs, a novel class of endogenous noncoding RNAs formed by a covalently closed loop, play an important role in oral cancer. However, the role of circ-0008798 and circ-0035967 in oral cancer remains unclear. Oral cancer has been considered as one of the major leading causes of cancer-related mortality. It involves different mechanisms and signaling pathways such as a MAPK pathway that comprises several key signalling components and phosphorylation events in tumorigenesis. The purpose of this study is to investigate the expression profile of circRNA in oral cancer tissue and explore the regulatory mechanism in oral cancer tumorigenesis. the present study, qRT-PCR was used to detect the expression of circ-0008798, circ-0035967 and map2k1 in 30 pairs of samples of oral cancer tissue and adjacent normal tissue.Significant upregulation of MAP2K1 gene was noted in the OLP (p value = 0.034), and OSCC (p value = 0.00), specimens compared with healthy controls. The expression level of circ-008798 and circ-0035967 expression was down-regulated in OSCC tissues (p value = 0.23), (p value = 0.00) and OLP tissues (p value = 0.088), (p value = 0.054).Moreover, the area under ROC curves (AUC) ofmap2k1 was 0.92, has_circ_0008798 was 1.00 (p < 0.001) and has_circ_0035967 was 0.99 (p < 0.001). Our data may help researchers to predict the molecular mechanisms of novel circ-0008798 and circ-0035967 in the development and progression of oral cancer comprehensively. Moreover, the present data indicate that novel circ-0008798 and circ-0035967 targets may be a series of promising candidates as biomarkers for oral cancer.